2018
DOI: 10.5479/si.1943-6688.102
|View full text |Cite
|
Sign up to set email alerts
|

Late Pleistocene (Rancholabrean) Mammalian Assemblage from Paw Paw Cove, Tilghman Island, Maryland

Abstract: Smithsonian Institution Scholarly Press

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Tropical species of bats are unknown from fossil deposits in the Florida peninsula after the early Miocene, except for a brief appearance of several species in the Pleistocene, including (Morgan et al, 1988;Morgan, 1991Morgan, , 2002: two species of Phyllostomidae, the vampire bats Desmodus archaeodaptes and D. stocki, both now extinct; two species of Mormoopidae, the extant Mormoops megalophylla and the extinct Pteronotus cf. pris-tinus; and a large living species of Molossidae, Eumops underwoodi.…”
Section: Taphonomy and Paleoecologymentioning
confidence: 99%
See 1 more Smart Citation
“…Tropical species of bats are unknown from fossil deposits in the Florida peninsula after the early Miocene, except for a brief appearance of several species in the Pleistocene, including (Morgan et al, 1988;Morgan, 1991Morgan, , 2002: two species of Phyllostomidae, the vampire bats Desmodus archaeodaptes and D. stocki, both now extinct; two species of Mormoopidae, the extant Mormoops megalophylla and the extinct Pteronotus cf. pris-tinus; and a large living species of Molossidae, Eumops underwoodi.…”
Section: Taphonomy and Paleoecologymentioning
confidence: 99%
“…Three species of molossids are recorded from the modern Florida fauna, the widespread Brazilian or Mexican free-tailed bat Tadarida brasiliensis, the Florida bonneted bat Eumops floridanus from southern peninsular Florida, and the velvety free-tailed bat Molossus molossus from the Florida Keys (Frank, 1997b;Marks and Marks, 2006). Eumops floridanus is endemic to the southern half of the Florida peninsula (Koopman, 1971;Timm and Genoways, 2004;Vannatta et al, 2021), and also has been identified from three late Pleistocene fossil deposits in southern Florida (Morgan, 1991(Morgan, , 2002. In fact, E. floridanus was originally described as the extinct species Molossides floridanus based on a mandible from the late Pleistocene Melbourne LF in Brevard County about midway along the Atlantic Coast of Florida (Allen, 1932), before it was discovered as a living animal in Miami at the southern tip of the peninsula (Barbour, 1936;Koopman, 1971).…”
Section: Taphonomy and Paleoecologymentioning
confidence: 99%